Jejak Jalur Rempah Nusantara dalam Catatan Sejarah Qatar - Karyadi, Fathurrochman (Faculty of Islam Nusantara, Nahdlatul Ulama University of Indonesia (Unusia) Jakarta., 2025)
This research explores Qatar’s strategic role in the spice trade route connecting the Nusantara (Southeast Asia) to the wider Islamic and global maritime world. Using Qaṭar fī ‘Uyūn al-Rahhālah by Ali Bin Ghanem Al-Hajri as the primary source, the study highlights Qatar not as a spice-producing region, but as a critical hub in the transcontinental exchange. According to Al-Hajri, Qatar functioned as a transit center where ships from the Far East, including those from the Malay Archipelago, would dock and unload valuable commodities such as spices, which were then redistributed to markets across the Middle East, North Africa, and Europe. In addition to Al-Hajri’s account, this research also draws on the maritime records of the renowned Arab navigator Ibn Majid. A comparative analysis between these two sources reveals overlapping patterns and shared understandings of the spice route. Arab traders, particularly those sailing the Indian Ocean, played a pivotal role in connecting the Nusantara with the Arabian Peninsula.By situating Qatar within this expansive historical and commercial context, the study contributes to the broader understanding of transregional trade networks. It sheds light on Qatar’s position not only as a passive recipient but as an active intermediary that facilitated intercultural and economic exchanges between East and West. Through this lens, the spice trade emerges not merely as a matter of goods, but as a conduit of civilizational contact—where Arab merchants and Southeast Asian cultures met, exchanged, and co-evolved.